Molecular drivers of lobular carcinoma in situ. Issue 1 (December 2015) - Logan, Greg; Dabbs, David; Lucas, Peter; Jankowitz, Rachel; Brown, Daniel; Clark, Beth; Oesterreich, Steffi; McAuliffe, Priscilla
Abstract Lobular carcinomain situ (LCIS) is considered to be a risk factor for the development of invasive breast carcinoma, but it may also be a non-obligate precursor to invasive lobular carcinoma (ILC). Many LCIS lesions do not progress to ILC, and the molecular changes that are necessary for progression from LCIS to ILC are poorly understood. Disruption in the E-cadherin complex is the hallmark of lobular lesions, but other signaling molecules, such as PIK3CA and c-src, are consistently altered in LCIS. This review focuses on the molecular drivers of lobular carcinoma, a more complete understanding of which may give perspective on which LCIS lesions progress, and which will not, thus having immense clinical implications.